Pengaruh CAR, ROA, ROE, Dan NPF Terhadap Total Aset Perbankan Syariah Di Bahrain, Arab Saudi, Brunei Darussalam, Malaysia, Dan Indonesia Tahun 2014-2021 - Taufik Riza Mahendra; Muhammad Wahid Musthofa (Jurnal Ilmiah Ekonomi Islam, 2023)
The Islamic banking industry is the Islamic financial industry that has the largest number of assets compared to other Islamic financial industries. This research was conducted to find out whether the variables CAR, ROA, ROE, and NPF can affect the total assets of Islamic banking. This research uses a quantitative-descriptive approach. CAR has a significant and positive effect on the total assets of Islamic banking. This means that if CAR increases, it will be followed by an increase in the total assets of Islamic banking. ROA has a significant effect on the total assets of Islamic banking. ROE has a significant and positive effect on the total assets of Islamic banking. This means that when ROE increases, it is followed by an increase in the total assets of Islamic banking. The NPF ratio has no significant effect on the total assets of Islamic banking. Simultaneously, it can be seen that the CAR, ROA, ROE, NPF ratios have a significant effect on the total assets of Islamic banking.